Complete issue - Comitato editoriale (Il Capitale Culturale: Studies on the Value of Cultural Heritage, 2018)
Complete Issue of the special issue n. 7/2018, Visualizing Past in a Foreign Country: Schiavoni / Illyrian Confraternities and Colleges in Early Modern Italy in comparative perspective